Morphology, phylogeography and drumming behaviour of a New Zealand ground weta, Hemiandrus pallitarsis : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Conservation Biology at Massey University, Palmerston North, New Zealand - Chappell, Esta Monique (Massey University, 2008)
Species are one of the fundamental components of biology and the accurate delimitation of species is important in evolutionary, systematic and ecological studies, yet there is still confusion over how species can be recognised. Examining different characters allows multiple lines of evidence for successful and accurate species delimitation and identification. In this thesis, morphological, genetic and behavioural variation is investigated within an endemic species of ground weta, Hemiandrus pallitarsis, in the North Island, New Zealand. Twelve morphological characters were measured, and mitochondrial cytochrome oxidase I DNA sequences were analysed from populations across the distributional range of H. pallitarsis. Both methods provide no evidence of a species complex within H. pallitarsis. Instead, the morphometric results suggest females are significantly larger than males, and ground weta in Palmerston North are significantly smaller than weta further north. Additionally, genetic analyses found substantial population structuring, large genetic distances, and an historical south to north pattern of movement in the North Island. The pattern of vibratory drumming behaviour followed that predicted by morphology and geographic proximity – drumming signals were more similar between geographically close populations and did not match the patterns of genetic isolation. Overall, this thesis was able to show that H. pallitarsis is morphologically, genetically and behaviourally variable across the North Island.
Keywords: Species identification; Genetic variation; Behavioural variation; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300800 Environmental Science::300805 Conservation